Metabolic profile alterations as early indicators of gastrointestinal stromal tumors (GISTs) recurrence and imatinib resistance - Luo, Allen Lin; Seylani, Allen; Haile, Yohannes; Sadighian, Assal; Sadighian, Sadaf; Agulnik, Mark (Journal of Gastrointestinal Oncology, 2026)
Background: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal (GI) tract. Despite surgery and adjuvant imatinib for high-risk cases, recurrence remains high, often due to resistance from secondary kinase mutations. Imatinib is known to influence lipid metabolism in GIST and chronic myeloid leukemia (CML). This study evaluates metabolic trends in recurrent GIST post-resection to determine whether these biomarkers can signal resistance or early recurrence.Methods: This retrospective cohort study utilized de-identified data from the TriNetX database, comprising over 200 million patients across 172 healthcare systems in 18 countries. We examined total cholesterol, triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), TG/HDL ratio, low-density lipoprotein cholesterol (LDL-C), hemoglobin A1c, body mass index (BMI), and thyroid-stimulating hormone (TSH) in 36 patients with recurrent GIST on imatinib.Results: Thirty-six patients were included in this study. Patients underwent resection an average of 25.9 months before recurrence. Total cholesterol increased significantly (R=0.92, P=0.03), while LDL-C showed a similar increasing trend (R=0.87, P=0.050). HDL-C decreased significantly between pre- and post-recurrence periods (P=0.03). BMI differed between pre- and post-recurrence periods (P=0.047). TG showed a strong positive correlation (R=0.93, P